+0  
 
0
248
1
avatar

–12(x + 6.2) = 60

Guest Apr 24, 2017
 #1
avatar+7342 
+2

-12(x + 6.2) = 60

 

Divide both sides of the equation by -12 .

x + 6.2 = 60/-12

 

x + 6.2 = -5

 

Subtract 6.2 from both sides of the equation.

x = -5 - 6.2

 

x = -11.2

hectictar  Apr 24, 2017

12 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.